Entrepreneurial Selves, Feminine Corporeality and Lifestyle Blogging in Singapore - Abidin, Crystal; Gwynne, J. (2017)
© 2017 by Koninklijke Brill NV, Leiden, The Netherlands. The making of the entrepreneurial self is a dominant trope of contemporary media culture, and a multitude of media formats across divergent national contexts showcase the contemporary obsession with media visibility and the attainment of celebrity status as the most aspirational form of social mobility. In Singapore, commercial lifestyle blogs are prime examples of entrepreneurial identity-making as websites almost exclusively created by young women, showcasing user-generated content oriented around the pleasures of consumption as a means of empowerment, self-actualisation and individualisation. By analysing content on a selection of blogs, this article aims to answer the following questions: To what extent are Singaporean women's identities contingent upon material consumption as a means of identity creation? How do blogs created by women demonstrate an entrepreneurial investment in their appearance and feminine corporeality as the means of perceived empowerment, even at the expense of more formal and structured forms of individualisation, such as education?.